Graphite nodules features identifications and damaging micromechanims in ductile irons - Alberto De Santis; Daniela Iacoviello; Vittorio Di Cocco (Fracture and Structural Integrity)
Ductile irons mechanical properties are strongly influenced by the metal matrix microstructure and on the graphite elements morphology. Depending on the chemical composition, the manufacturing process and the heat treatments, these graphite elements can be characterized by different shape, size and distribution. These geometrical features are usually evaluated by the experts visual inspection, and some commercial softwares are also available to assist this activity. In this work, an automatic procedure based on an image segmentation technique is applied: this procedure is validated not only considering spheroidal graphite elements, but also considering other morphologies (e.g. lamellae).